BIMBINGAN BELAJAR UNTUK SEKOLAH DASAR PADA MASA PANDEMI - Anita Munawwaroh; Erfitra Rezqi Prasmala; Melani Babang Noti (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
The purpose of this Potential-Based Community Service (PMBP) activity was to provide tutoring to elementary school students in Rindi Village Rw 002 in East Sumba Regency. This service activity used the method of preparation, implementation, and evaluation. The results and outcomes achieved, namely, the tutoring activities that we did were certainly different from activities in general. In addition, our free tutoring activities were meant to provide guidance on emotional and psychomotor aspects, as well as prioritized cognitive aspects. We adopt a relaxed learning concept in order to help elementary school students feel more comfortable and not to feel bored when participating in tutoring activities.